The effect of in-situ electrochemical grafting of KH-792 onto carbon fibers on surface properties - Yan-lin Li; Chong-pan Ma; Xiao-lei Sun; Qi-hang Lou; Yuan-jian Tong; Yu Wang (Carbon Trends, 2025)
Carbon fibers(CFs) have a carbon content as high as 90 % and exhibit chemical inertness on their surface. They must undergo surface activation treatment before being used as a reinforcing phases in composite materials. In this study, in-situ electrochemical grafting technology was employed to link the molecules of γ-aminoethyl aminopropyltrimethoxysilane (KH-792), which had undergone hydrolysis condensation, onto the surface of polyacrylonitrile (PAN)-based CFs. The effect of electrochemical grafting of KH-792 on the surface physical and chemical structure and properties of the CFs were investigated through testing methods such as X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, single-filament tensile, and dynamic contact angle (DCAT). The results indicated that after electrochemical grafting with a KH-792/NH4HCO3 composite electrolyte, the number of oxygen-containing and nitrogen-containing groups on the fiber surface was significantly increased, resulting in improved surface wettability of carbon fibers. Electrochemical grafting and acid ion etching lead to a slight decrease in the degree of graphitization (R) of carbon fibers, but the mechanical properties remain stable After treatment with KH-792 under 3 mA·cm−2 current density conditions, KH-792 treatment resulted in a peak of active functional group content on the surface of carbon fibers. Consequently, the interfacial shear strength (IFSS) value of carbon fiber reinforced epoxy based composites increased by 56 %.